Righteous gentiles: religion, identity and myth in John Hagee’s Christians United for Israel by Sean Durbin - Kirchner, Anna Maria (PentecoStudies, 2020)
DURBIN, Sean. Righteous Gentiles: Religion, Identity and Myth in John Hagee’s Christians United for Israel. Leiden: Brill, 2019. 274pp. Hbk. ISBN: 9789004384958. $167.
Keywords: Rezension